Analysis of the Characteristics of Chemical Compounds in Palm Flour (Arenga pinnata) from the Poso District - Poima , Deswita K.; Abraham, Paulus H. (Universitas Tadulako, 2023)
Aren (Arenga pinnata) is a palm family with the potential to develop high economic value in tropical regions such as Indonesia. This study aims to determine the levels of each chemical compound contained in palm flour (protein, fat, carbohydrate, potassium, and calcium levels). Determination of protein, fat, and carbohydrate levels in this study using a UV - VIS spectrophotometry tool. Determination of potassium (K) and calcium (Ca) levels using a flame photometer. The results showed that the analysis of protein content obtained 1.5765 %, fat content obtained 1.465 %, and carbohydrate content obtained 55.88 %. The analysis of potassium content obtained 1.76 %, and calcium levels obtained 1.495 %. The results of this study are expected to be foodstuffs that can be processed into food to meet the needs of protein, carbohydrates, fat, potassium, and calcium in the body.